Oscillometric measurement of the ankle-brachial index and the estimated carotid-femoral pulse wave velocity improves the sensitivity of an automated device in screening peripheral artery disease - Fendrik, Krisztina; Biró, Katalin; Endrei, Dóra; Koltai, Katalin; Sándor, Barbara; Tóth, Kálmán; Késmárky, Gábor (Frontiers in Cardiovascular Medicine, 2023)
To overcome time and personnel constraints of the Doppler-method, automated, four-limb blood pressure were recently developed. Their additional functions, such as measuring the estimated carotidfemoral pulse wave velocity (ecfPWV) have been thus far, less studied. We aimed to compare the sensitivity and specificity of different ankle-brachial index (ABI), toebrachial index (TBI) and ecfPWV measurement methodologies to evaluate their contribution to peripheral artery disease (PAD) screening. Methods Among 230 patients (mean age 64±14 years) ABI measurement was performed using a Doppler device and manual sphygmomanometer; Doppler ABI was calculated by taking the higher, modified Doppler ABI by taking the lower systolic pressure of the two ankle arteries as the numerator, the denominator was the higher systolic pressure between both brachial arteries. The automated ABI measurement was carried out using the automatic BOSO ABI-system 100 PWV device, which also measured ecfPWV. TBI was obtained using a laser Doppler fluxmeter (Periflux 5000) and a photoplethysmographic device (SysToe). To assess atherosclerotic and definitive PAD lesions, vascular imaging techniques were used, including ultrasound in 160, digital subtraction angiography in 66 and CT angiography in 4 cases.ROC analysis exhibited a sensitivity/specificity of 70.6/98.1% for the Doppler ABI (AUC=0.873), 84.0/94.4% for the modified Doppler ABI (AUC=0.923), 61.5/97.8% for the BOSO ABI (AUC=0.882) at a cut-off of 0.9. Raising the cut-off to 1.0 increased the sensitivity of BOSO to 80.7%, with the specificity decreasing to 79.1%. The ecfPWV measurement (AUC=0.896) demonstrated a 63.2/100% sensitivity/specificity in predicting atherosclerotic lesions at a cut-off of 10 m/s. Combining BOSO ABI and ecfPWV measurements recognized 89.5% of all PAD limbs.The combined BOSO ABI and ecfPWV measurement may help in selecting patients requiring further non-invasive diagnostic evaluation for PAD. The user-friendly feasibility may make it suitable for screening of large populations.